The influence of hydrogen peroxide on the growth, development and quality of wax apple (Syzygium samarangense, [Blume] Merrill & L.M. Perry var. jambu madu) fruits - Khandaker, Mohammad Moneruzzaman; Boyce, Amru Nasrulhaq; Osman, Normaniza (Elsevier, 2012)
The present study represents the first report of the effect of hydrogen peroxide (H2O2) on the growth, development and quality of the wax apple fruit, a widely cultivated fruit tree in South East Asia. The wax apple trees were spray treated with 0, 5, 20 and 50 mM H2O2 under field conditions. Photosynthetic rates, stomatal conductance, transpiration, chlorophyll and dry matter content of the leaves and total soluble solids and total sugar content of the fruits of wax apple (Syzygium samarangense, var. jambu madu) were significantly increased after treatment with 5 mM H2O2. The application of 20 mM H2O2 significantly reduced bud drop and enhanced fruit growth, resulting in larger fruit size, increased fruit set, fruit number, fruit biomass and yield compared to the control. In addition, the endogenous level of H2O2 in wax apple leaves increased significantly with H2O2 treatments. With regard to fruit quality, 20 mM H2O2 treatment increased the K+, anthocyanin and carotene contents of the fruits by 65%, 67%, and 41%, respectively. In addition, higher flavonoid. phenol and soluble protein content, sucrose phosphate synthase (SPS), phenylalanine ammonia lyase (PAL) and antioxidant activities were recorded in the treated fruits. There was a positive correlation between peel colour (hue) and TSS, between net photosynthesis and SPS activity and between phenol and flavonoid content with antioxidant activity in H2O2-treated fruits. It is concluded that spraying with 5 and 20 mM H2O2 once a week produced better fruit growth, maximising the yield and quality of wax apple fruits under field conditions. (C) 2012 Elsevier Masson SAS. All rights reserved.